2014
DOI: 10.1007/s10841-014-9742-5
|View full text |Cite
|
Sign up to set email alerts
|

A burning desire for smoke? Sampling insects favoured by forest fire in the absence of fire

Abstract: Fire-favoured insects are difficult to sample except opportunistically after forest fires. Here, we tested if smoke from a small fire could be an efficient way to sample such insects. Insects were sampled over ca. 10 h hours, by hand-picking and netting on screens put up around the fire. Two specimens of the rare and redlisted Hormopeza spp. (Diptera, Empididae) were caught. Large numbers ([20,000) of Microsania spp. (Diptera, Platypezidae) were caught, but none in the absence of smoke. The numbers of Microsan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The virescens group counts the highest number of burn‐associated species. Moreover, Cortinicara gibbosa (Herbst) is considered as opportunistic in the eastern Canadian boreal forest, but this Holarctic species has been identified as fire‐favoured in Sweden (Lundberg, ; Wikars, ; Milberg et al ., ). This group could thus be considered to be more at risk when it comes to the salvage logging effect due to its close association with fire‐killed trees.…”
Section: Discussionmentioning
confidence: 99%
“…The virescens group counts the highest number of burn‐associated species. Moreover, Cortinicara gibbosa (Herbst) is considered as opportunistic in the eastern Canadian boreal forest, but this Holarctic species has been identified as fire‐favoured in Sweden (Lundberg, ; Wikars, ; Milberg et al ., ). This group could thus be considered to be more at risk when it comes to the salvage logging effect due to its close association with fire‐killed trees.…”
Section: Discussionmentioning
confidence: 99%
“…Such behavioral changes could be due to underlying health effects (Erb et al 2018) or serve to limit exposure to airborne toxins (Singer et al 1989, Dickinson et al 2009, Liu et al 2021b. Some species rely on smoke as an early-warning signal that helps them to avoid wildfires (Engstrom 2010, Höcherl and Tautz 2015, Álvarez-Ruiz et al 2021) or prepare to conserve energy in a post-fire landscape (Geiser et al 2018), whereas others use smoke as a cue to navigate toward newly available resources in burned habitats (Schütz et al 1999, Klocke et al 2011, Milberg et al 2015. Animals could also change their behavior in response to alterations in the physical environment that result from smoke pollution (Cheyne 2008, Lee et al 2017), such as reduced visibility (Haider et al 2019) or cooler air temperatures (Robock 1991).…”
Section: Behavioral Responsesmentioning
confidence: 99%
“…Pyrophilous insects (i.e. fire-associated species that benefit from resources available in post-fire landscapes) can use smoke as a cue to navigate toward fires, responding to thermal and/or olfactory signals (Schütz et al 1999, Klocke et al 2011, Álvarez et al 2015, Milberg et al 2015. Some are even known to swarm in smoke plumes, such as 'smoke flies' of the genera Microsania and Hormopeza, possibly to mate near burned trees where they deposit their eggs (Evans 1966, Snoddy and Tippins 1968, Sinclair and Cumming 2006.…”
Section: Resource Availabilitymentioning
confidence: 99%
“…Frogs possess specialized hearing organs for detecting—and fleeing from—fire ( Grafe et al 2002 ); this adaptation has been suggested as a possibility in arthropods of the LLPE ( Dell et al 2017 ) for fire detection in both positively and negatively pyrotaxic species. As smoke can be used as an efficient trapping method for some pyrophilic flies [though not pyrophilic beetles ( Milberg et al 2015 )], these species may use it to locate recently burned host material. In Europe, the black fire beetle Melanophila acuminata (DeGeer) (Coleoptera: Buprestidae) possesses infrared receptors to detect still-smoldering logs for oviposition, as larvae require freshly fire-killed trees ( Evans 1966 , Schmitz and Bleckmann 1998 ).…”
Section: Arborealmentioning
confidence: 99%